Environmental, Social, Governance (ESG) and Islamic Finance: A Review - Abdillah Arif Nasution; Darwis Harahap; Mimma Maripatul Uula (Management and Sustainability, 2022)
This study aims to look at the development of research on Environmental, Social, Governance (ESG) and Islamic finance and research path that can be carried out based on journals published on this theme. This study used a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "ESG & Islamic Finance", which comes from the Scopus database with a total of 44 journal articles. Then, the data is processed and analyzed using the VosViewer application to know the bibliometric map of “ESG & Islamic Finance” research development worldwide. The study results found that in the bibliometric author mapping, the authors who published the most research on the theme “ESG & Islamic Finance” were Ahmed A and Hassan M.K.; Chiaramonte I. Furthermore, based on the bibliometric keyword mapping, 4 clusters can become research lines with topics related to Sustainable Banking and Corporate Social Responsibility (ESG), Management of Financial Risk and the Impact of COVID-19, Financial Sustainability and Environment-Based Sharia Investment and The Role of Islamic Finance and Achieving the SDGs, and the words most used are Islamic Finance, Islamic Bank, and Environment.